Roma Communities in Međimurje, Croatia: From Spatial Segregation toward Spatial Integration and Back - Šlezak, Hrvoje (Geographica Pannonica, 2023)
Spatial segregation of Roma population is a dynamic category that changes its characteristics over time. This paper investigates changes in indicators of spatial segregation of the Roma national minority in Međimurje, the northernmost county of the Republic of Croatia. The spatial analysis of Roma in the researched area, based on the last three consecutive population censuses, indicates changes in the Roma distribution patterns. Through the last two inter-census periods, spatial dispersion of the Roma population is noticeable as a beginning of more intensive spatial integration process. On the other hand, quantitative indicators point to the conclusion that spatial segregation as a phenomenon and fundamental feature of Roma population is increasing.
Keywords: Međimurje; Roma; spatial segregation; integration; Croatia